Why Academic Writing? - Gurung, Raj Kumar (Pursuits: A Journal of English Studies, 2022)
Yes, writing is really a challenging and a tough work. Academic writing is a technical writing. It differs from general writing. It is a coherent writing of good organization of words, phrases, sentences, paragraphs, ideas and issues, whereas general writing is just the record of something like the data of information. They cannot be put in the same bucket. In academic writing, ideas and details are well combined so that the readers will not be confused to get the intended information. The general writing does not follow all these requirements. Academic writing means the incorporation of organizing, drafting and revising. Chronological order of all the elements is what academic writing is.